Identifying Outcome Measures for Migraine Value‐Based Contracting Using the Delphi Method. Issue 10 (30th September 2020) - Swart, Elizabeth C. S.; Good, Chester B.; Henderson, Rochelle; Manolis, Chronis; Yanta, Claire; Parekh, Natasha; Neilson, Lynn M.
Abstract : Objective: To identify meaningful migraine outcome measures among key stakeholders to inform value‐based contracts for migraine medications. Background: Value‐based contracts linking medication payments to predefined performance metrics aim to promote value through aligned incentives and shared risk between manufacturers and payers. The emergence of new and expensive pharmaceuticals for migraine presents an opportunity for value‐based contract development. However, uncertainty remains around which outcomes are most meaningful to all migraine stakeholders. Methods: This study utilized a Delphi survey to incorporate views from 82 stakeholders, including patients (n = 21), providers (n = 23), payers (n = 10), employers (n = 18), and pharmaceutical company representatives (n = 10). A list of 15 migraine‐related outcomes was created from a literature review and subject matter expert consultation. Stakeholders reported on the value of these outcomes through a 5‐point Likert scale and selection of their top 3 most meaningful outcomes. All participants except patients and employers also used a 5‐point Likert scale to rate the feasibility of collecting each outcome measure. Consensus was defined as ≥75% agreement on the importance and feasibility of an outcome (Likert scores ≥4/5 or selection of an outcome as most meaningful). Results: After 2 rounds, consensus was achieved for importance of 9 outcomes on the Likert scale. "Decrease in migraine frequency" reached 100% agreement (82/82), followed by "increased ability to resume normal activities" (96%, 79/82). When asked to choose the 3 most meaningful outcomes, stakeholders selected "decrease in migraine frequency" (88%, 72/82) followed by "decrease in migraine severity" (80%, 66/82). The 2 measures rated as most feasibly collected were "decrease in emergency department/urgent care visits" (95%, 40/42) and "decrease in migraine frequency" (90%, 38/42). There were statistically significant differences between non‐patient and patient stakeholders in selection of "decrease in emergency department/urgent care visits" [20% (12/61) vs 0% (0/21), P  = .031]; and employer and patient stakeholders in selection of "decrease in work days missed" [44% (8/18) vs 5% (1/21), P  = .006] and "decrease in emergency department/urgent care visits" [22% (4/18) vs 0% (0/21), P  = .037] as most meaningful outcomes. Conclusions: The measures "decrease in migraine frequency" followed by "decrease in migraine severity" were identified as top priority migraine outcome measures.